Analisis Kualitas Pelayanan Publik Di Perusahaan Daerah Air Minum Cabang Selatan Kota Semarang - Wijanarko, Candra; Sulandari, Susi; Yuniningsih, Tri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The aim of this research is to analyze the level of quality of service, to analyze people’s satisfaction and to analyze public satisfaction index about Water Supply Company in the southern branch office of Semarang. This research uses qualitative descriptive method. The source of the data in this study is a questionnaire with the number of respondents 150 people which are selected by using accidental sampling method. Based on the results seen from 14 dimensions of community satisfaction (IKM) are service procedures, service requirements, clarity of service officer, disciplinary care of service officer, the responsibilityof service officer, the ability of service officer, speed of service, justice to get the service, friendliness of service officer, reasonableness of the service charge, certainty of service schedule, environmental comfort and environmental safety. It is showed that the service performance of Water Supply Company in the southern branch office of Semarang is ‘Good’, this is seen from the public Satisfaction Index value of 2.95 with conversion value of 73,6. From these percentages seen that all units of the average quality of service is good. The conlcusion of this research is the values of IKM index from 14 dimensions of community satisfaction is the average of all elements is good. The Suggestion can be given thatthere are several service dimensions that urged to promptly repaired, such as a service requirements and service schedule certainty in Water Supply Company in the southern branch office of Semarang.